The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1044/2017_aja-17-0018
|View full text |Cite
|
Sign up to set email alerts
|

Readability Level of Spanish-Language Patient-Reported Outcome Measures in Audiology and Otolaryngology

Abstract: Purpose: The purpose of this study was to examine the readability level of the Spanish versions of several audiology-and otolaryngology-related patient-reported outcome measures (PROMs) and include a readability analysis of 2 translation approaches when available-the published version and a "functionalist" version-using a team-based collaborative approach including community members. Method: Readability levels were calculated using the Fry Graph adapted for Spanish, as well as the FernandezHuerta and the Spaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 42 publications
0
10
0
2
Order By: Relevance
“…We then reviewed each of the translations, our own and those from the professional firms (15 documents, in total) to assess reading ease and grade level using several variations of the Flesch Reading Ease score 28 adapted for Spanish written materials, including the Fernández-Huerta index, 29 which is one of the oldest and most commonly used readability formulas in Spanish. 30 …”
Section: Methodsmentioning
confidence: 99%
“…We then reviewed each of the translations, our own and those from the professional firms (15 documents, in total) to assess reading ease and grade level using several variations of the Flesch Reading Ease score 28 adapted for Spanish written materials, including the Fernández-Huerta index, 29 which is one of the oldest and most commonly used readability formulas in Spanish. 30 …”
Section: Methodsmentioning
confidence: 99%
“…In another study, Coco et al researched the effect of the translation approach on readability. 13 They found that translations of a patient-reported outcome measure created with a functionalist approach had better readability than published counterparts that revealed a more literal, nonfunctionalist approach. 14 We conducted a study to draw attention to translation approach as a factor influencing translation results by investigating the effect of specific approaches on user response (and, ultimately, on participant engagement), demonstrating that different approaches result in translations that differ in reader response, some being more user friendly and preferable for certain text types than others.…”
Section: E R H E R Hmentioning
confidence: 99%
“…), Chinese (Chen et al (2013); Jiang et al (2018); Sun et al (2014), etc. ), Spanish (Coco et al (2017);I. Parkeret al (2001); Spaulding (1956), etc.…”
Section: Introductionmentioning
confidence: 99%